Changes in dietary intake, chronotype and sleep pattern upon Ramadan among healthy adults in Jeddah, Saudi Arabia: A prospective study - Alzhrani, Ameera; Alhussain, Maha H.; BaHammam, Ahmed S. (Frontiers in Nutrition, 2022)
Background: Notable lifestyle changes can occur in Ramadan due to the sudden shift in eating routine with fasting during daylight hours. This study aimed to examine the changes in dietary intakes, chronotype, sleep pattern, and physical activity level before and during Ramadan in healthy adults. Methods: This study was conducted in Jeddah city, Saudi Arabia, and convenience sampling was used. To compare dietary, chronotype and sleep pattern changes before and during Ramadan, data were collected in two separate periods: the first period was two months before Ramadan, and the second period was during the last three weeks of Ramadan. Dietary intake was assessed using 24-hour food recall and chronotype using Morningness-Eveningness Questionnaire. Daytime sleepiness and sleep duration were assessed using the Epworth sleepiness scale and a sleep diary for seven consecutive days, respectively. Anthropometric measurements were also taken across the study periods. Results: Results: A total of 115 adults (96 females and 19 males) were included in the study. Significant increases in daily calorie and carbohydrate intakes during Ramadan than before Ramadan were noted (calorie intake: 1482.9±536.4 kcal/day before Ramdan vs. 1635.5±635.1 kcal/day during Ramadan; carbohydrate intake: 180.8±72.1 g/day before Ramadan vs. 202.6±88.7 g/day during Ramadan; p < 0.05). Chronotypes and daytime sleepiness were also associated significantly with Ramadan fasting. A significant slight reduction in body weight during Ramadan was observed (66.4±18.1 kg before Ramdan vs. 66.1±17.8 kg before Ramadan and during Ramadan, respectively; p < 0.05). Conclusion: This study indicates that Ramadan diurnal fasting was associated with greater calorie and carbohydrate intake, changes in chronotype, and daytime sleepiness. The study also suggests that Ramadan diurnal fasting model may be a promising weight loss strategy.